The effect of lipocalin-2 (LCN2) on apoptosis: a proteomics analysis study in an LCN2 deficient mouse model - Dongming Wu; Xiaopeng Wang; Ye Han; Yayun Wang (BMC Genomics, 2021)
Abstract Background Recent studies have shown that lipocalin-2 (LCN2) has multiple functions involved in various biological and pathological processes including energy homeostasis, cancer, inflammation, and apoptosis. We aimed to investigate the effect of LCN2 on apoptosis that influences the pathogenetic process of metabolic diseases and cancer. Methods We performed a proteomics analysis of livers taken from LCN2-knockout mice and wild type mice by using label-free LC-MS/MS quantitative proteomics. Results Proteomic analysis revealed that there were 132 significantly differentially expressed proteins (49 upregulated and 83 downregulated) among 2140 proteins in the liver of LCN2-knockout mice compared with wild type mice. Of these, seven apoptosis-associated proteins were significantly upregulated and seven apoptosis-associated proteins downregulated. Conclusion Proteomics demonstrated that there were seven upregulated and seven downregulated apoptosis-associated proteins in liver of LCN2-knockout mice. It is important to clarify the effect of LCN2 on apoptosis that might contribute to the pathogenesis of insulin resistance, cancer, and various nervous system diseases.